2006
DOI: 10.1302/0301-620x.88b10.17587
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of the acetabular component

Abstract: We compared the orientation of the acetabular component obtained by a conventional manual technique with that using five different navigation systems. Three surgeons carried out five implantations of an acetabular component with each navigation system, as well as manually, using an anatomical model. The orientation of the acetabular component, including inclination and anteversion, and its position was determined using a co-ordinate measuring machine. The variation of the orientation of the acetabular componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…There are 3 types of imaging systems used to simultaneously generate different planes of the target object, all of which need intraoperative registration of anatomical landmarks (Sikorski and Chauhan 2003). Either CT-based, fluoroscopically-assisted, or imageless methods are used to simultaneously generate different planes of the therapeutic object to be treated (Grutzner et al 2004, Widmer and Grutzner 2004, Ottersbach and Haaker 2005, Honl et al 2006, Kalteis et al 2006a). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are 3 types of imaging systems used to simultaneously generate different planes of the target object, all of which need intraoperative registration of anatomical landmarks (Sikorski and Chauhan 2003). Either CT-based, fluoroscopically-assisted, or imageless methods are used to simultaneously generate different planes of the therapeutic object to be treated (Grutzner et al 2004, Widmer and Grutzner 2004, Ottersbach and Haaker 2005, Honl et al 2006, Kalteis et al 2006a). …”
Section: Introductionmentioning
confidence: 99%
“…inclination of 40° ± 10°, anteversion of 15° ± 10°) (Lewinnek et al 1978) when using a freehand technique (Saxler et al 2004a, Tannast et al 2005a, Honl et al 2006, Kalteis et al 2006a, Bosker et al 2007, Leichtle et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…12,13 Honl et al compared acetabular cup orientation between five different computer-assisted navigation systems for total hip arthroplasty and demonstrated significant differences among them. 12 In addition, Carli et al compared the accuracy of intraoperative measurements to postoperative tibial and femoral alignment in two different computer-assisted systems for total knee arthroplasty and found a significant difference in the outcome as well. 13 Interestingly, several clinical studies have demonstrated high accuracy rates of pedicle screw placement using CT-based navigation compared with other methods, such as freehand technique and fluoroscopic navigation.…”
Section: Discussionmentioning
confidence: 99%
“…At present, computer navigation system seems to be a most reliable tool for cup positioning [8, 10, 26, 27]. However, the use of this system is not widely adopted due to its high costs, complexity and operating time, and individual studies are too small to allow conclusive statements on the potential benefit.…”
Section: Discussionmentioning
confidence: 99%